Milestones of Asian Rhinoplasty - Fakhro, Abdulla (Semin Plast Surg, 2015)
The field of plastic surgery originally developed out of the necessity to reconstruct the human body after the destruction of war. However, injured soldiers were not the only people who desired a change in appearance. After World War II, many people in Asian countries sought to attain a more Western look through surgery. Along with eyes, the nose was the main focus for these cosmetic procedures. In this article, the authors examine the evolution of Asian rhinoplasty from its original description in 1964 to the present. The characteristic anatomical differences between the Western and Asian nose are identified in relation to the technical challenges for rhinoplasty surgeons. Then the benefits and risks of the two major surgical approaches, autograft versus alloplast, are detailed. Finally, the coevolution of techniques and implant usage is traced from a dorsum-only implant, to an L-shaped implant, a cartilaginous cap graft with a one-piece rhinoplasty, an I-shaped implant, and a two-piece augmentation rhinoplasty. Outlining these changes demonstrates the advancement of the field of plastic surgery and the growing expectations of the patient. These advancements have provided the tools necessary to better align a patient's aesthetic goals and their unique anatomical presentation with a specific surgical approach.